Strategy to Create a Private Banking Hub - A Case Study of Singapore - PUAY, Eng-Chuan (2008)
The growing affluence in the Asian economy has triggered many large banking corporations to establish a stronger presence in Asia to tap the growing needs for wealth management services. In particular, the area of private banking services has been in the spotlight recently with many reports quoting that only one third of the high net worth individualsÃÂÃÂ¢ÃÂÃÂÃÂÃÂ (HNWI) asset worth about US$8.4 trillion in Asia (PriceWaterhouseCoopers 2006) is professionally managed by private banks.